1997
DOI: 10.1038/sj.bjp.0700970
|View full text |Cite
|
Sign up to set email alerts
|

Visual detection of transport‐P in peptidergic neurones

Abstract: Hypothalamic peptidergic neurones possess an uptake process for amines (transport‐P), for which prazosin is a substrate. It is characterized by a paradoxical increase in the accumulation of [3H]‐prazosin when the concentration of unlabelled prazosin is increased above 10−7 m. This increase is due to activation of a proton‐dependent, vacuolar‐type ATPase‐linked pump that is blocked by tricyclic antidepressants. This study utilized a fluorescence method to detect amine uptake in individual cells. Prazosin is flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 15 publications
(24 reference statements)
1
16
0
Order By: Relevance
“…Further, following accumulation by Transport‐P, retention of the amines in peptidergic neurones requires maintenance of intracellular acidity ( Shen & Al‐Damluji, 1997 ). A microscopic method for detection of Transport‐P revealed that a fluorescent analogue of prazosin accumulated in peptidergic neurones in a granular distribution and that this process could be inhibited by chloroquine ( Al‐Damluji et al ., 1997 ). This indicated that these amines accumulate in acidified intracellular vesicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, following accumulation by Transport‐P, retention of the amines in peptidergic neurones requires maintenance of intracellular acidity ( Shen & Al‐Damluji, 1997 ). A microscopic method for detection of Transport‐P revealed that a fluorescent analogue of prazosin accumulated in peptidergic neurones in a granular distribution and that this process could be inhibited by chloroquine ( Al‐Damluji et al ., 1997 ). This indicated that these amines accumulate in acidified intracellular vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable amount of evidence supported this second part of the hypothesis. Thus: (a) the paradoxical increase in binding of [ 3 H]‐prazosin is inhibited competitively by antidepressants which are known to inhibit the pre‐synaptic re‐uptake of amines ( Al‐Damluji et al ., 1993 ; Al‐Damluji & Kopin, 1996b ); (b) the paradoxical increase in accumulation of [ 3 H]‐prazosin was not seen in membrane preparations, indicating that it requires intact cells or storage organelles ( Al‐Damluji et al ., 1993 ); (c) the prazosin paradox is an energy‐dependent process, the source of energy being the electrochemical proton gradient which is generated by vacuolar‐type ATPase (V‐ATPase; Al‐Damluji & Kopin, 1996a ); (d) ligands for Transport‐P must possess a specific chemical structure, consisting of a hydrophobic phenyl group, an alkyl side chain and a basic amine ( Al‐Damluji & Kopin, 1998 ); (e) a fluorescent analogue of prazosin accumulated in intracellular vesicles, providing visual evidence for uptake ( Al‐Damluji et al ., 1997 ); (f) following accumulation by Transport‐P, the amines can be released by an energy‐dependent process ( Shen & Al‐Damluji, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore studied the accumulation of [ 3 H]‐verapamil, which is a phenylethylamine derivative which possesses the structural properties which enable interaction with transport‐P, as identified in this study. [ 3 H]‐verapamil was internalized by GnRH cells in a similar manner to prazosin (Al‐Damluji, 1996). Further, phenylethylamine and its derivatives inhibited the uptake of prazosin competitively (Figure 8), suggesting that these compounds and prazosin act on the same transport‐P carrier molecule in GnRH neurones.…”
Section: Discussionmentioning
confidence: 83%
“…(3) Uptake 2 accumulates a wide range of compounds, including 5‐HT, histamine and isoprenaline (Grohmann & Trendelenburg, 1984) which do not interact with transport‐P (Table 1), indicating that transport‐P is more selective in its substrate spectrum than Uptake 2 . Thus, transport‐P differs from Uptake 2 in its neuronal location (Al‐Damluji et al , 1997), functional properties (Al‐Damluji & Kopin, 1996a) and in the structure of its ligands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation